Pertumbuhan dan Produksi Tiga Varietas Unggul di Lahan Rawa Lebak Desa Jambu Ilir Kabupaten Ogan Komering Ilir, Sumatera Selatan - Suparwoto Suparwoto (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2019)
Suparwoto et al, 2019.Â The Growth and Production Three Rice Superior Varieties in Swampy LandsÂ at the Jambu Ilir Village, Ogan Komering Ilir District. JLSO 8(1):39-46.The assessment was carried out in Jambu Ilir Village, Tanjung Lubuk District, Ogan Komering Ilir Regency, South Sumatra, starting in the dry season of 2018. Varieties exhibited were 2 superior varieties Â and 1 comparative variety, Mekongga. The aim of the study was to obtain information on the growth and production of Inpari 30 and Inpara 8 varieties that were adaptive and had high production on lebak lands. The study was designed by observation method, spacing of legowo 2: 1 (50x25x12.5 cm), seedling age 35 days after seedling, 2-3 seeds / holes. The dosage of fertilizer used is 150 kg Urea, 100 kg SP-36 and 100 kg KCl / ha. The variables observed were: plant height, number of productive tillers, number of grain per panicle, number of filled grains per panicle, and grain yield per ha. The data obtained was arranged in tabulation and analyzed by statistical tests, namely the test of the mean value (test-t). The results showed that the plant height of the varieties exhibited was classified as low to moderate with the number of productive tillers classified as moderate. Inpari 30, and Inpara 8 can adapt well in lebak lands with a production of 5.1-5.3 tons GKP / ha higher than Mekongga as a comparison variety and are highly favored by farmers.